Kompetensi Mengajar Calon Guru SD (Studi Kasus Mahasiswa Program Studi PGSD FKIP Universitas Muhammadiyah Palangkaraya) - Ady Ferdian Noor; Fazakkir Noor (Anterior Jurnal, 2014)
The method used qualitative research methods case study type. This qualitative study using this type of case research strategy. Riduwan (2005) suggested Qualitative Methods is a research method that is used to examine the condition of scientific objects, where the researcher is a key instrument. Qualitative research uses the natural environment as a data source directly. Situation good education within the family, school, and community, as it is (naturally) without any changes and intervention by the researcher, is the object of qualitative research. Silalahi (2003: 62) and Sudjana and Ibrahim (2001: 69-71) argues the case study are (a) a study that will involve us in a more in-depth investigation and a thorough examination of the behavior of an individual, (b) research on the background rear and conditions of individuals, groups, or communities with the aim to provide a complete picture of the subject or event under study, and (c) a study conducted intensive, detailed and in-depth on the organism, institution or certain symptoms. This case study is used as the subject under study narrow and limited. The results of the research that students Studies Program PGSD FKIP Muhammadiyah University of Palangkaraya year class of 2012 perform individual tasks and task groups is seen that the ability to teach students, especially in terms of confidence, dare to appear, the sound loud and clear and the characters / characteristic that has not been fully owned also less able to control the situation and condition of class.